A comparative analysis of Ibn Sina and Al- Ghazali: their philosophical underpinnings and contributions toward Muslim education - Ariffin, Adlina (2011)
Islamic Civilisation has witnessed the blossoming and diversification of intellectual and scientific achievements through its varied prominent scholars and thinkers. This paper focuses on two of the most distinguished among them – Ibn Sina and Al-Ghazali. The main aim of the paper is to analyse and accentuate the similarities and differences in both scholars’ theoretical underpinnings and its effects on the pursuit of knowledge. The paper begins by explicating the concept of knowledge from the Islamic perspective. This is followed by descriptions on the backgrounds of both scholars and a comparison of their theoretical foundation. The paper concludes that the juxtaposition of these scholars definitely brings out their similarities while simultaneously highlights their point of divergent. Both scholars displayed a very close relationship between their intellectual quest and the recognition of God as the Ultimate Truth. This relationship is not only evident in their writings and thoughts but also in their personal conduct.